Review of ‘Imamate Caliphate’ and the Emphasis of Appointment from the Perspective of Reason and Narration - Keramtifard, Mahin (International Journal of Psychosocial Rehabilitation, 2020)
The issue of the divine appointment of Imamate and Caliphate is one of the most fundamental differences between the Shia and the Sunni Muslims, which has many rational and narrative reasons. The significance of this issue in the Muslim world is so much that if it had been done in accordance with divine will, one could accept that among the divine religions, the religion of Islam would have had the least disputes. The Sunnis do not use a coherent method in the field of Imamate and Caliphate and their beliefs in this regard are contradictory. In general, they believe that Imamate and leadership are not the principles of religion, but they are a subcategory of religion. They do not consider a significant religious and ideological position for them ,they describe the caliph as the religious ruler of the Islamic Ummah and reject the evidence based on rational and narrative reasons. According to Shia beliefs, Imamate and caliphate are divine positions and one of the five principles in the religion of Islam. They argue that Imamate is like prophecy, is a divine position that God Almighty should determine the Imam. The results of this article also show that the two main denominations of Islam (Shia and Sunni) have basic differences in terms of Imamate and caliphate. According to the rational arguments (the arguments of grace, the ultimate cause, higher possibility and comprehensive manifestation proof) and the narrative arguments (inference from the explicit verses of the Holy Qur'an), including the verses of (propagation, perfection of religion and disappointment of disbelievers and Velayat and Oli al-Amr" and “Hadith of Mazilat, Hadith of Thaqalain and Hadith of Ghadir” the divine appointment of Imamate and caliphate could be proved by rational and narrative reasons.